Treatment of Refractory Small Bowel Bleeding With Thalidomide after Living Donor Kidney Transplantation. (July 2018) - Park, Hyung Sub; Heo, Yoonjung; Kim, Daehwan; Yoo, Kwon Cheol; Shin, Chang Sik; Lee, Taeseung
Abstract : Introduction: Small bowel bleeding after kidney transplantation is a complication that can occur from long-term multiple immunosuppressant use that can be fatal if it is not managed appropriately. We present a case of intractable small bowel bleeding that was treated successfully with thalidomide after multiple failed attempts of embolization and small bowel surgical resection. Case: A 65-year-old male patient with diabetic nephropathy underwent living donor kidney transplantation. The patient received the kidney from his daughter, who was a blood group-compatible donor. Immunosuppressive therapy consisted of tacrolimus, mycophenolic acid, and steroids. On the 11th day of post-operation, the patient developed severe melena for which he received massive red blood cell transfusions due to unstable vital signs. The dose of immunosuppressants was also reduced to half of the standard dose. However, the patient developed more frequent hematochezia. Concurrent gastroscopy, colonoscopy and abdominal computed tomographic angiography showed active bleeding from the proximal jejunum. Therefore the patient underwent laparoscopic small bowel segmental resection. Unfortunately, hematochezia recurred 4 days after the first re-operation. Mycophenolic acid was ceased and tacrolimus was replaced by cyclosporine A. Diffuse bleeding from multiple ulcerative lesions between the jejunum and the ileum was detected by balloon enteroscopy. A second re-operation was performed which consisted of a laparoscopy-assisted small bowel resection with double barrel ileostomy. Despite these attempts, the patient showed deteriorated melena through the ileostomy 7 days after the second re-operation. Repeated enteroscopy was performed through the ileostomy and evidence of diffuse bleeding at the duodenal 3rd portion was found, together with multiple superficial ulcerations and tendency for angiodysplasias. This time, embolization of the branches of the pancreaticoduodenal artery was performed, and the procedure successfully stabilized the patient's vital signs. The decision was made to introduce a new medical therapy to prevent recurrent small bowel bleeding of the patient as the ACG (American College of Gastroenterology) Clinical Guideline suggested. We initiated thalidomide 100 mg/day after obtaining informed consent from the patient's family. The patient's small bowel bleeding was no longer evident after treatment with thalidomide. Conclusion: Several studies have shown the successful outcome of thalidomide treatment on obscure gastrointestinal bleeding due to angiodysplasia, but this is the first study to describe its effect on post-transplant patients.